Ateljee Hännätön kissa. - Isomäki, Ahti; Jaukkuri, Maaretta; Kaitavuori, Kaija; Kalha, Harri; Puhakka, Anneli (Helsinki : KIASMA Museum of Contemporary Art, 2002)
This book discusses people with intellectual disability as members of a community and artists, and it opens up perspectives on their art. In her contribution, Anneli Puhakka of the Finnish Association on Mental Retardation addressed the changing position of intellectually disabled people and the fleeting boundary between ability and disability. In an interview, the artist Ahti Isomäki, instructor in the arts at Kirsikoti, tells of his work with the intellectually disabled. The essay In search of lost time, by Harri Kalha, PhD, discusses the works of disabled artists and their processes of working with reference to the values of the art world.
Engels & Fins
Ateljee Hännätön kissa / Studio Bobtailed Cat, KIASMA (Museum of Contemporary Art) Helsinki. 2002-08-17. 2002-10-13
boek
Keywords: Eronen, Päivi; Leppänen, Nina; Levy, Jukka-Pekka; Mikkonen, Kirsi; Paalamo, Marika; Papunen, Mervi; Puustinen, Kati; Ronkainen, Hanna; Tanskanen, Eeva; Turunen, Pekka; Vaarala, Pia